Asymmetric lateral coherence of OAM radiation reveals topological charge and local curvature. (14th June 2018) - Paroli, B; Cirella, A; Drebot, I; Petrillo, V; Siano, M; Potenza, M A C
Abstract: We show that phase properties and the local curvature of a wavefront with orbital angular momentum can be measured by the real part of the complex degree of coherence of radiation obtained with respect to an off-axis fixed point (asymmetric lateral coherence). The method can be implemented by exploiting a scan of double-slits along Cartesian axis. Because the method exploits simple apertures, it can be applied to measure topological and phase properties of stable sources in a wide range of wavelengths from microwaves to x-rays.